2023
DOI: 10.3390/children10060964
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychomotor Therapy among Children with Graphomotor Impairment with and without DCD-Diagnosis

Abstract: In Switzerland, psychomotor therapy (PMT) is a standard treatment for children with graphomotor impairments, but scientific evidence of its effectiveness is rare. To investigate the effectiveness of PMT, we conducted a randomised field trial (RFT). The sample consisted of 121 first and second graders with graphomotor impairments, some of whom met the criteria of developmental coordination disorder, while the remaining suffered from developmental dysgraphia. The treatments lasted over 5 months. Handwriting flue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Research focusing on writing difficulties in children with DCD found that over 80% of them experience challenges in writing compared to typically developing children [7][8][9]. These challenges include slow writing and illegibility [10][11][12][13]. There are various methods 2 of 19 for acquiring writing skills and treating children who struggle with writing, including those within the population of children with DCD (e.g., the Cognitive Orientation to Daily Occupational Performance program [14] and neuromotor task training [15]).…”
Section: Introductionmentioning
confidence: 99%
“…Research focusing on writing difficulties in children with DCD found that over 80% of them experience challenges in writing compared to typically developing children [7][8][9]. These challenges include slow writing and illegibility [10][11][12][13]. There are various methods 2 of 19 for acquiring writing skills and treating children who struggle with writing, including those within the population of children with DCD (e.g., the Cognitive Orientation to Daily Occupational Performance program [14] and neuromotor task training [15]).…”
Section: Introductionmentioning
confidence: 99%